Complex Decision-Making in Economy and Finance - Massotte, Pierre; Corsi, Patrick (Innovation, entrepreneurship and management series, 2020)
Pertinent to modern industry, administration, finance and society, the most pressing issue for firms today is how to reapproach the way we think and work in business. With topics ranging from improving productivity and coaxing economic growth after periods of market inactivity, Complex Decision-Making in Economy and Finance offers pragmatic solutions for dealing with the critical levels of disorder and chaos that have developed throughout the modern age. This book examines how to design complex products and systems, the benefits of collective intelligence and self-organization, and the best methods for handling risks in problematic environments. It also analyzes crises and how to manage them. This book is of benefit to companies and public bodies with regards to saving assets, reviving fortunes and laying the groundwork for robust, sustainable societal dividends. Examples, case studies, practical hints and guidelines illustrate the topics, particularly in finance.